Interfacial Grown Zinc Oxide Origami Structure for Broadband Visible Light Driven Photocatalysts (Adv. Mater. Interfaces 29/2022). Issue 29 (19th October 2022) - Jia, Guobin; Hupfer, Maximilian; Schulz, Martin; Schmidl, Gabriele; Dellith, Andrea; Diegel, Marco; Müller, Robert; Dellith, Jan; Lindner, Florian; Dietzek‐Ivanšić, Benjamin; Plentz, Jonathan
Abstract : Interfacial Growth of Zinc Oxide As reported by Guobin Jia and co‐workers in article number 2200936, ZnO origami structures comprising of quasi 2D ZnO nanosheets show very broad band visible light‐driven photocatalytic activity, verified by monochromatic LED light sources. The visible light‐driven photocatalytic effect is attributed to the carriers generated through the interband defect levels (IDLs) and fast carrier migration to the surface, so that the competing carrier recombination at IDLs is diminished.